On the approximation by the poynomials of S. M. Bershtein type of the Hursa problem for nonlinear equation of hyperbolic type - Makhmudov , A. P.; Le Dyk Kiem (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Using Bernshtein type polynomials for functions of two variables, a scheme is given for successive approximations, and its uniform convergence to the unique solution of the Goursat problem for a nonlinear hyperbolic equation is proved.